Cost-Effective Adjustments to Nursing Home Staffing to Improve Quality. (June 2020) - Bowblis, John R.; Roberts, Amy Restorick
Health care providers face fixed reimbursement rates from government sources and need to carefully adjust staffing to achieve the highest quality within a given cost structure. With data from the Certification and Survey Provider Enhanced Reports (1999-2015), this study holistically examined how staffing levels affect two publicly reported measures of quality in the nursing home industry, the number of deficiency citations and the deficiency score. While higher staffing consistently yielded better quality, the largest quality improvements resulted from increasing administrative registered nurses and social service staffing. After adjusting for wages, the most cost-effective investment for improving overall deficiency outcomes was increasing social services. Deficiencies related to quality of care were improved most by increasing administrative nursing and social service staff. Quality of life deficiencies were improved most by increasing social service and activities staff. Approaches to improve quality through staffing adjustments should target specific types of staff to maximize return on investment.